Social Responsibility Trends in Industries, Over the Last 15 Years. A Systematic Review - Gonzales Abanto, Wilson Alcides; Delgado Mestanza, Jose Leodan; Chavez Delgado, Juhny Giunmy; Horna Salas, José Eduardo; Tello Zavala, Aurorita Melissa Maricielo; Diaz Diaz, Alexis Antonio; Culqui Chavez, Marco Antonio; Quispe Vasquez, Luis Roberto (LACCEI, 2024)
Corporate social responsibility is an inclusive term, where companies seek to adopt practices that improve the environment and society. This Systematic Review talks about the trends of Social Responsibility in industries, with the aim of answering the research question: "What are the trends of social responsibility in the industry?". The methodology used is based on the PRISMA declaration, which establishes criteria for the collection of information. Keywords were defined in Spanish, such as "Corporate Social Responsibility", and Boolean operators were applied in various databases, such as ProQuest, Scopus, Redalyc , Ebsco, Dialnet and Scielo. The search focused on articles published between 2008 and 2023. Inclusion criteria were also developed to select articles from scientific and academic journals in Spanish and English. After the review, 33 articles that met the criteria were finally selected. The results showed that the majority of articles came from Scopus, followed by ProQuest and Dialnet. Regarding trends, the categorization table highlights eleven different sectors, evidencing the importance of Social Responsibility to achieve objectives and satisfy society